A study of the level of job satisfaction among the employees of Malaysian Mosaics Berhad, Petaling Jaya / Mohamad Fauzan Abas - Abas, Mohamad Fauzan (Faculty of Business and Management, 2011)
The main purpose of this study is to explore the relationships among satisfaction with supervisor, compensation, co-workers and company management to job satisfaction. Based upon the research findings, suggestions and also recommendations would be offered. This study is accomplished with the process of literature analysis and questionnaires that have been distributed to 50 respondents that worked in Malaysian Mosaics Berhad. Based on the literature analysis from data of first hand and second hand, it helps to offer fundamental and theoretical guidelines for this research to be conducted and conclude Descriptive Research has been adopted for this research, primary data and secondary data are used in finding the data in doing the research. Apart from that, questionnaire that consist of 16 questions were distributed to the respondent while adopting the convenience sampling in getting the respondents. The relevant steps are used for investigation on the current level of job satisfaction among the employees of Malaysian Mosaics Berhad. Finally, the author will use SPSS to analyze data in order to answer the research objective that have been established as it will analyse the data and help give in depth answer on the research objective. Lastly, the research is concluded with the relevant answer in order to improve the level of job satisfaction level of the employees of job satisfaction.